Penerapan Media Pembelajaran Animasi Berbasis Animaker untuk Peningkatan Pemahaman Siswa Kelas VIII dalam Pembelajaran PAI di SMP Al-Madina Wonosobo - Diyah Citraning Kasih; Noor Aziz; Pamungkas Stiya Mulyani (STIKes Ibnu Sina Ajibarang, 2024)
This research evaluates the effectiveness of using Animaker-based animation learning media to enhance the understanding of eighth-grade students in Islamic Education at SMP Al-Madina Wonosobo. The study employs a quantitative approach with a quasi-experimental design. Findings indicate that the use of Animaker significantly improves students' understanding, as evidenced by notable improvements between pretests and posttests, supported by statistical analyses. Recommendations include school leadership support in fostering a conducive learning environment, teachers' enhanced creativity in selecting appropriate teaching models, and active student engagement in the learning process. The research aims to provide practical guidance for educators to improve Animaker-based Islamic Education teaching methods at SMP Al-Madina Wonosobo and contribute to the development of more effective teaching methodologies overall.